Rural tourism in Kiulu, Sabah, Malaysia: a critical examination through the lens of the host community - Saikim, Fiffy Hanisdah; Chong, Franey Joseph; Salleh, Norhuda; Pengiran Bagul, Awangku Hassanal Bahar; Mohd. Nordin, Nordiana; Abdul Aziz, Nor Akmar; Khaled, Jamshed; Prideaux, Bruce; Richard, Baizura; Engchuan, Angeline; Jimit, Julinus Jeffrey (Universiti Malaysia Sabah, Institute for Tropical Biology and Conservation, 2025)
Local communities often face a number of challenges when seeking to participate in rural tourism including participation in decision making, the level of empowerment the community enjoys and other factors including knowledge of tourists and local culture and the role governments play in supporting rural tourism development. To investigate these issues, a mixed methods approach was used to collect data from 118 residents of Kiulu, a rural destination in Sabah, Malaysia through questionnaires and in-depth interviews. The results show that successful rural tourism in Kiulu is driven by strategies that promote local participation in decision-making, community empowerment and better knowledge of the tourism industry. However, the study also shows that there is a lack of positive correlation between rural tourism growth and knowledge sharing, a challenge that appears to be rooted in strained relationships between tourism stakeholders. Other barriers include financial constraints, inadequate road access and the need for specialised training in tourism services. Addressing these barriers through targeted government interventions such as financial support and capacity building programmes may help distribute the benefits of rural tourism more equitably and ultimately promote sustainable development within the community.